PERBANDINGAN KINERJA INDEKS SAHAM SYARIAH DENGAN INDEKS KONVENSIONAL PERIODE 2011-2016 (STUDI KASUS PADA ISSI DAN IHSG) - SHOLIHAH, AMINATUS (Jurnal Ilmu Manajemen (JIM), 2017)
In past few years in Indonesia has grown sharia investment. Sharia-based instrument is an alternative that can be used by society to invest, especially the Moslem community of Indonesia which is a major community. Significant developments that occurred in sharia investment products, especially in the capital market. The purpose of this research is to find out comparison of Indonesia Sharia Stock Index (ISSI) with Jakarta Composite Index (JCI) in period 2011 to 2015 using Sharpe, Treynor and Jensen method. The type of this research is descriptive research using quantitative data.Sample determination using saturated sample method.The data in this research is secondary data in the form of ISSI stock price index and JCI stock price index every month in period 2011 until 2015.The results based on the Sharpe method calculation shows that the ISSI index has better performance than the JCI index.The performance of ISSI index is supported by the sharia capital market regulation as stipulated in Fatwa No.40/DSN-MUI/X/2003.While based on Treynor method, ISSI index also has better performance if it compared to JCI index. The performance of the ISSI index is supported by the performance of the JII index (constituent of ISSI index) which experienced an increase in stock prices and net income from company that are listed.And based on the Jensen method, the ISSI index and JCI index did not show any advantage because the effect of market conditions in 2011-2016. Keywords: ISSI index, JCI index, Sharpe, Treynor, Jensen